Die Außenpolitik der Vereinigten Staaten von Amerika und ihr Bekenntnis zum multilateralen Internationalismus - Thomas Peter Salzmann (Historia.scribere)
U.S. foreign policy and its commitment to multilateral internationalism In the present paper I will argue that the Truman and the Eisenhower Administration, in dealing with post-war Germany, the Soviet Union and the Cold War, followed a policy of multilateral internationalism. After having introduced this concept in the first part, the second part will deal with the question whether the reorientation that George W. Bush has brought about in U.S. foreign policy has fundamentally altered its basic focus on multilateral internationalism. Based on an analysis of Barack Obama's foreign policy it will be argued against such an alleged profound change.